Immersive, Secure, and Collaborative Air Quality Monitoring - José Marinho; Nuno Cid Martins (Computers)
Air pollution poses a serious threat to both public health and the environment, contributing to millions of premature deaths worldwide each year. The integration of augmented reality (AR), blockchain, and the Internet of Things (IoT) technologies can provide a transformative approach to collaborative air quality monitoring (AQM), enabling real-time, transparent, and intuitive access to environmental data for community awareness, behavioural change, informed decision-making, and proactive responses to pollution challenges. This article presents a unified vision of the key elements and technologies to consider when designing such AQM systems, allowing dynamic and user-friendly immersive air quality data visualization interfaces, secure and trusted data storage, fine-grained data collection through crowdsourcing, and active community learning and participation. It serves as a conceptual basis for any design and implementation of such systems.